THE EFL STUDENTS’ PROBLEM IN THEIR ORAL PRESENTATION - Zumrotul Rohmawati; Khoirunnisa, Nur Winda; Mansur, Mansur (Prosiding SNasPPM, 2022)
Oral presentation is one of class activities which used frequently by collage students to increase their speaking skill. However, each activity always has its problem in the implementation, so does oral presentation activity. This study aimed to know the problem faced by the fourth semester students of English language Education in their oral presentation activity at University PGRI Ronggolawe. A descriptive method was used to carry out the study. For gathering data, observation and questionnaire were used. The result of the study shows that the biggest problems faced by the students in their presentation are: lack of vocabulary, anxiety, and not confident. Another problem they have faced is grammatically error.